Multi-dimensional oscillatory activity of mouse GnRH neurons in vivo - Su Young Han; Shel-Hwa Yeo; Jae-Chang Kim; Ziyue Zhou; Allan E Herbison (eLife)
The gonadotropin-releasing hormone (GnRH) neurons represent the key output cells of the neural network controlling mammalian fertility. We used GCaMP fiber photometry to record the population activity of the GnRH neuron distal projections in the ventral arcuate nucleus where they merge before entering the median eminence to release GnRH into the portal vasculature. Recordings in freely behaving intact male and female mice revealed abrupt ~8 min duration increases in activity that correlated perfectly with the appearance of a subsequent pulse of luteinizing hormone (LH). The GnRH neuron dendrons also exhibited a low level of unchanging clustered, rapidly fluctuating baseline activity in males and throughout the estrous cycle in females. In female mice, a gradual increase in basal activity that exhibited ~80 min oscillations began in the afternoon of proestrus and lasted for 12 hr. This was associated with the onset of the LH surge that ended several hours before the fall in the GCaMP signal. Abrupt 8 min duration episodes of GCaMP activity continued to occur on top of the rising surge baseline before ceasing in estrus. These observations provide the first description of GnRH neuron activity in freely behaving animals. They demonstrate that three distinct patterns of oscillatory activity occur in GnRH neurons. These are comprised of low-level rapid baseline activity, abrupt 8 min duration oscillations that drive pulsatile gonadotropin secretion, and, in females, a gradual and very prolonged oscillating increase in activity responsible for the preovulatory LH surge.